2005
DOI: 10.1515/advg.2005.5.2.301
|View full text |Cite
|
Sign up to set email alerts
|

New counterexamples to A. D. Alexandrov’s hypothesis

Abstract: The paper presents a series of principally di¤erent C y -smooth counterexamples to the following hypothesis on a characterization of the sphere: Let K H R 3 be a smooth convex body. If at every point of qK, we have R 1 c C c R 2 for a constant C, then K is a ball. (R 1 and R 2 stand for the principal curvature radii of qK.)The hypothesis was proved by A. D. Alexandrov and H. F. Mü nzner for analytic bodies. For the case of general smoothness it has been an open problem for years. Recently, Y. Martinez-Maure ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 10 publications
0
27
0
3
Order By: Relevance
“…Firstly, the existence of such a surface (even without additional properties) is far from obvious. However, some candidates already exist in the literature, see [7,9]. Secondly, the existence of a regular triangulation is a strong condition: numerical experiments showed that all previously constructed saddle surfaces either cannot be regularly triangulated, or the existence of a regular triangulation is hard to establish.…”
Section: Lemma 26 the Surface F Is A Saddle And Flat At Each Vertexmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, the existence of such a surface (even without additional properties) is far from obvious. However, some candidates already exist in the literature, see [7,9]. Secondly, the existence of a regular triangulation is a strong condition: numerical experiments showed that all previously constructed saddle surfaces either cannot be regularly triangulated, or the existence of a regular triangulation is hard to establish.…”
Section: Lemma 26 the Surface F Is A Saddle And Flat At Each Vertexmentioning
confidence: 99%
“…The ingredients of the proofs are the theory of virtual polytopes [14,9,10], the combinatorial rigidity theory, and the theory of pseudo triangulations [15,5] applied to the spherical case in [13]. In the proofs we essentially use three different representations of virtual polytopes: as convex chains, as piecewise linear (support) functions, and as stressed spherically embedded graphs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A different (and simpler) proof of 7.7 is given in Section 7.4 for the case of Laman graphs. 44 GÜNTER ROTE, FRANCISCO SANTOS, AND ILEANA STREINU 7.2. Stretching Combinatorial Pseudo-Triangulations.…”
Section: Theorem 77 For Every Planar Topological Embedding Of a Rigmentioning
confidence: 99%
“…in the area of art galleries (illumination by floodlights) [61]; and in an area which, at first sight, may seem unrelated to discrete geometry: the construction of counter-examples to a conjecture of A. D. Alexandrov characterizing the sphere among all smooth surfaces [44].…”
Section: Introductionmentioning
confidence: 99%